The MET(T)A Protocol: Mindfulness and EMDR Treatment Template for Agencies - Stephen Dansiger; Roshni Chabra; Lauren Emmel; Justine Kovacs (SAGE Publishing, 2020)
Evidence indicating the relationship between trauma and substance use disorders (SUDs), in addition to relapse and treatment retention rates for this population, suggests there is a need for a trauma-focused solution to treat SUDs. Eye movement desensitization and reprocessing (EMDR) therapy has been studied extensively as an effective approach for treating trauma and Posttraumatic Stress Disorder (PTSD). The research evaluating its treatment for other mental health disorders such as SUDs is promising. Merging mindfulness and ethical mindfulness practices with EMDR therapy lends additional evidence-based elements to make the case for this integrative system of treatment to be studied as a trauma-focused primary psychotherapy to treat SUDs. The resulting treatment, the MET(T)A Protocol (Mindfulness and EMDR Treatment Template for Agencies), has been created to address the need for a trauma-focused solution to treat SUDs. Procedures of the MET(T)A Protocol as applied in each of the 8 phases of EMDR therapy are described in detail. Clinical examples are provided to explain the application of the MET(T)A Protocol.